2011
DOI: 10.1038/embor.2011.209
|View full text |Cite
|
Sign up to set email alerts
|

CD8αα and ‐αβ isotypes are equally recruited to the immunological synapse through their ability to bind to MHC class I

Abstract: Bimolecular fluorescence complementation was used to engineer CD8 molecules so that CD8aa and CD8ab dimers can be independently visualized on the surface of a T cell during antigen recognition. Using this approach, we show that CD8aa is recruited to the immunological synapse almost as well as CD8ab, but because the kinase Lck associates preferentially with CD8ab in lipid rafts, CD8aa is the weaker co-receptor. During recognition of the strong CD8aa ligand H2-TL, CD8aa is preferentially recruited. Thus, recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
(55 reference statements)
0
17
1
Order By: Relevance
“…CD8a–GFP×2 and CD8a–GFP×3 were essentially undetectable at cilia (), implying that the ciliary membrane diffusion barrier has a cytosolic size-exclusion limit of 50–100 kDa (considering that CD8a forms a homodimer; Rybakin et al, 2011), similar to the value observed for soluble proteins (Kee et al, 2012). …”
Section: Resultsmentioning
confidence: 57%
“…CD8a–GFP×2 and CD8a–GFP×3 were essentially undetectable at cilia (), implying that the ciliary membrane diffusion barrier has a cytosolic size-exclusion limit of 50–100 kDa (considering that CD8a forms a homodimer; Rybakin et al, 2011), similar to the value observed for soluble proteins (Kee et al, 2012). …”
Section: Resultsmentioning
confidence: 57%
“…4, A and B), indicating that the TCR interaction with nonstimulatory pMHCI was at most a minor determinant of coagonism for OT-I T cells. We also noted that recruitment of CD8 to the immunological synapse (Yachi et al, 2005;Rybakin et al, 2011) was unperturbed by the sc-K b VSV-TCRm mutation (not depicted).…”
Section: Reduction In Cd8-binding Affinity For Agonist Pmhci Enforcesmentioning
confidence: 82%
“…The CD8 coreceptor's interaction with nonstimulatory MHCI has been suggested to be important for coagonism in MHCI-restricted cells (Yachi et al, 2005;Gascoigne, 2008;Gascoigne et al, 2010). Nonstimulatory pMHC alone can recruit CD8 to the T cell-APC interface (Yachi et al, 2005;Rybakin et al, 2011). Also, coagonist pMHCs became antagonists in CD8-negative cells (Stone et al, 2011).…”
Section: Development Of Inducible Antigenic Sc-mhcmentioning
confidence: 99%
“…14,15 The signalling role of the CD8 a-chain can be enhanced by palmitoylation of the CD8 b-chain at a membrane-proximal cysteine. 16 Palmitoylation at this site allows the recruitment of the tripartite TCR-CD3-CD8 signalling complex to detergent-insoluble membrane domains, or lipid rafts. 17,18 Lipid rafts are made up of ordered microdomains, enriched with sphingolipids and cholesterol, that exclude molecules such as phosphatases (CD45) but recruit molecules that are critical for T-cell activation, such as p56 Lck and the linker for activation of T cells.…”
Section: Co-receptor Functions Of Cd8mentioning
confidence: 99%
“…This interaction leads to a signalling cascade that recruits ZAP‐70 to the TCR–CD3 complex, leading to the amplification or enhancement of T‐cell activation signals . The signalling role of the CD8 α‐chain can be enhanced by palmitoylation of the CD8 β‐chain at a membrane‐proximal cysteine . Palmitoylation at this site allows the recruitment of the tripartite TCR–CD3–CD8 signalling complex to detergent‐insoluble membrane domains, or lipid rafts .…”
Section: Introductionmentioning
confidence: 99%